Upregulated TRPC3 and Downregulated TRPC1 Channel Expression during Hypertension is Associated with Increased Vascular Contractility in Rat - Noorani, Muzamil M.; Noel, Rebecca C.; Marrelli, Sean (Frontiers in Physiology, 2011)
Transient receptor potential C1 and C3 (TRPC1 and TRPC3) are expressed in vascular smooth muscle cells and are thought to be involved in vascular contractility. In the present study, we determined the effect of systemic hypertension on TRPC1/TRPC3 channel expression and vascular contractility in rat carotid artery (CA). CA were studied from male spontaneously hypertensive (SHR), Wistar Kyoto (WKY) and Long-Evans (LE) rats. TRPC1/3 expression was determined by RT-PCR and Western blot. TRP channel function was evaluated by whole cell patch clamp, using UTP (60 µM) to stimulate TRPC1/3 channels. Contractions of endothelium-denuded CA segments to UTP (1 – 300 µM) and phenylephrine (Phe; 0.1 nM-10 µM) were measured in an isometric tension bath. TRPC1 and TRPC3 mRNA was present in CA of both WKY and SHR. Western blot demonstrated 3.1 ± 1.2 times greater TRPC3 expression and 0.5 ± 0.2 times TRPC1 in SHR versus WKY CA. Isolated CA showed potentiated contraction to UTP in the SHR versus WKY. Activation of voltage-dependent Ca2+ channels (VDCC) in UTP-mediated constriction only occurred in SHR CA. Contraction to Phe was unaltered between WKY and SHR CA and involved equal significant VDCC activation in both groups. Patch clamp demonstrated that the UTP-stimulated current (Iutp) was greater in SHR compared to the normotensive WKY and LE rats with peak Iutp (at -110 mV) of -63 ± 24 pA compared to -25 ± 4 pA, respectively. We demonstrate that UTP-mediated but not Phe-mediated constrictions are potentiated in the CA during hypertension. Expression of TRPC1 is decreased whereas TRPC3 is increased in SHR CA. Interestingly, VDCC activation only contributes to UTP-mediated contraction of SHR CAs whereas it contributes substantially and equally in Phe-mediated contraction. We speculate that the alteration of TRPC channel expression in hypertension leads to greater smooth muscle depolarization, VDCC activation, and vascular contractility in the UTP (but not Phe) signaling pathway.